Kerjasama Bilateral Indonesia-Malaysia dalam Perspektif Ekonomi: Perlindungan Pekerja Migran Indonesia di Malaysia dari Perdagangan dan Penyelundupan Manusia - Vivi Hana Pertiwi (GLOBAL SCIENTS PUBLISHER, 2025)
The bilateral cooperation between Indonesia and Malaysia encompasses not only economic and political aspects but also addresses a crucial social issue—namely, the protection of Indonesian migrant workers. The rampant occurrence of human trafficking and smuggling has elevated the protection of Indonesian migrant workers (TKI) as a key agenda in the bilateral relationship between the two countries. This study employs a qualitative descriptive method through literature review and official documentation, aiming to examine the dynamics of bilateral cooperation in combating exploitative practices against migrant workers. The main findings reveal that despite several Memoranda of Understanding (MoUs) and inter-agency coordination efforts, human trafficking continues due to weak oversight, legal loopholes, and bureaucratic corruption. This study underscores the urgent need for stronger and more comprehensive bilateral diplomacy to ensure the human rights and full protection of Indonesian migrant workers.